Analysis of hydrodynamic forces on high-head slide gates using CFD (2018)
Coefficients that can be applied to current analytical expressions that predict the hydrodynamic forces and, particularly, the downpull phenomenon on an inverted 30° lip gate at a bottom outlet of a dam, were determined from Computational Fluid Dynamics (CFD) simulations. Two slide gates were simulated: A typical 45° lip used for model validation and the inverted 30° lip. These simulations made use of the VOF (Volume Of Fluid) multiphase model, embedded in the commercial software ANSYS FLUENT, to simulate the air and water interaction in the free surface flow downstream of the gate. The CFD predictions were successfully validated against those by analytical expressions that related the water discharge through the gate and the gate opening at a fixed reservoir head. The predicted downpull was in agreement with that obtained from analytical expression for the well-studied 45° lip gate. Through the validated CFD simulation it was possible to determine the coefficients for the analytical calculation of downpull on the inverted 30° gate, which were not available in the state-of-the-art analytical expressions. The methodology here described can easily be applied to different gate geometries for which design coefficients are not available.